Altered states: The effects of media and technology on the creative process in advertising agencies. Issue 1 (2nd January 2019) - Stuhlfaut, Mark W.; Windels, Kasey
Abstract: The media environment has changed dramatically due to the explosion of new channels and technological innovations, which has had important ramifications not only for advertising, but also for advertising agencies and their creative processes. Using a series of interviews with agency creative directors and digital strategists, this study investigated how agencies have addressed these challenges and taken advantage of the opportunities. Its two key contributions are an updated model of the creative process and the identification of four alternative structures agencies use to create the core concept. The study also found a paradigm shift from framing technology in terms of its production value, to framing technology in terms of its strategic and creative value, as technology specialists have become involved in the strategic and creative stages of campaign development.